(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, a penalty finite element method is presented for the two dimensional stationary conduction-convection problems. The existence and the convergence of the penalty stationary conduction-convection formulation are shown. An optimal error estimate of the numerical velocity, pressure and temperature is provided for the penalty finite element method when the parameters є and h are sufficiently small. Our numerical experiments show that our method is effective and our analysis is right.